PENGEMBANGAN MEDIA PETUALANG MEMBACA BERBASIS STEM PADA MATERI MEMBACA PERMULAAN SISWA KELAS I SDN OEBOBO 2 KOTA KUPANG - Tirsa De Jesus, Laurdes; E. Noya Nahak, Kristina; Abdullah, Abdurahman (STKIP Subang, 2026)
This study aims to develop a STEM-based “Petualang Membaca” learning media for beginning reading materials for first-grade students at SDN Oebobo 2 Kupang City. The study was motivated by the low reading ability of students, which is indicated by difficulties in recognizing letters, forming syllables, and the low interest in reading due to the use of conventional learning media. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects involved 25 first-grade students. Data collection instruments included pretest and posttest to measure improvements in beginning reading skills, validation questionnaires for material, media, and language experts, and practicality questionnaires for teachers and students. Data analysis techniques included validation, practicality, and effectiveness analysis. The effectiveness of the media was analyzed using the Paired Sample t-Test and normalized gain (N-Gain) test. The results showed that the STEM-based “Petualang Membaca” media obtained very good validation results with scores of 84% from material experts, 91% from language experts, and 94% from media experts. The media was also considered very practical based on positive responses from teachers (89%) and students (90%). In addition, students’ learning outcomes increased, with the average pretest score of 67.2 rising to 87.6 in the posttest. The Paired Sample t-Test showed a significant difference (Sig. = 0.000 < 0.05), while the N-Gain test indicated that 68% of students experienced moderate improvement and 32% experienced high improvement. Keywords: learning media; STEM; beginning reading; elementary school